Venlafaxine Induced Spontaneous Ejaculation: A Case Report (Journal of Psychiatrists' Association of Nepal, 2025)
Venlafaxine, an antidepressant classified as a serotonin-norepinephrine reuptake inhibitor (SNRI), is commonly associated with side effects such as dizziness, nausea, nervousness, drowsiness, and sexual dysfunction. These side effects are typically dose-dependent and more common at higher doses. This case highlights a rare occurrence of spontaneous ejaculation linked to venlafaxine at a relatively low dose, underscoring the importance of recognizing that such side effects can appear even at lower therapeutic levels.